Separation-enrichment method for airborne disease spores based on microfluidic chip - Wang, Yafei; Zhang, Xiaodong; Yang, Ning; Ma, Guoxin; Du, Xiaoxue; Mao, Hanping (International Journal of Agricultural and Biological Engineering, 2021)
Airborne diseases are likely to cause crop yield reduction, which has aroused widespread concern. In this study, a two-stage separation-enrichment structure microfluidic chip with compound field for separation and enrichment the greenhouse crops airborne disease spores directly from gas flow was developed. The chip is mainly composed of three parts: arc structure pretreatment channel, semicircular electrode structure and collection tank. COMSOL 5.1 software was used to simulate the designed microfluidic chip. 30 µm particles were used to represent P. xanthii spores, 25 µm particles were used to represent P. cubensis spores, and 16 µm particles were used to represent B. cinerea spores. The simulation results showed that the separation and enrichment efficiency of 16 μm particles, 25 μm particles, and 30 μm particles was 88%, 91%, and 94%, respectively. The experimental verification results were observed under a microscope. The results showed that separation and enrichment efficiency of B. cinereal spores, P. cubensis spores and P. xanthii spores was 75.7%, 83.8% and 89.4%, respectively. As a result, the designed microfluidic chip can be used to separate and enrich the spores of airborne diseases of greenhouse crops, which can provide a basis for the research of real-time monitoring technology for greenhouse airborne diseases. Keywords: greenhouse, crop disease, airborne spore, microfluidic chip DOI: 10.25165/j.ijabe.20211405.6375 Citation: Wang Y F, Zhang X D, Yang N, Ma G X, Du X X, Mao H P. Separation-enrichment method for airborne disease spores based on microfluidic chip. Int J Agric & Biol Eng, 2021; 14(5): 199–205.